2016
DOI: 10.3390/soc6020018
|View full text |Cite
|
Sign up to set email alerts
|

The Portrayal of Occupational Therapy and Occupational Science in Canadian Newspapers: A Content Analysis

Abstract: Abstract:The primary goal of occupational therapy is to enable people to participate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…To answer the research questions, the University of Calgary's Proquest online database Canadian Newsstream was used as a source, a database consisting of n = 300 English Language Canadian newspapers, for its complete time range from 1980 to March 2018. Canadian newspapers were chosen because (a) existing and potential speech-related professionals are readers of newspapers, (b) the database comprises over 300 news sources including all regions of Canada, (c) over 75% of Canadians still read newspapers [52,53], and as such are influenced by what they read and (d) parents, teachers, and career counselors who often give advice on career ideas to young adults also are readers of newspapers [54].…”
Section: Newspapersmentioning
confidence: 99%
“…To answer the research questions, the University of Calgary's Proquest online database Canadian Newsstream was used as a source, a database consisting of n = 300 English Language Canadian newspapers, for its complete time range from 1980 to March 2018. Canadian newspapers were chosen because (a) existing and potential speech-related professionals are readers of newspapers, (b) the database comprises over 300 news sources including all regions of Canada, (c) over 75% of Canadians still read newspapers [52,53], and as such are influenced by what they read and (d) parents, teachers, and career counselors who often give advice on career ideas to young adults also are readers of newspapers [54].…”
Section: Newspapersmentioning
confidence: 99%
“…For example, an Australian study on public perception of physiotherapy reported that while the public knew that physiotherapists work with musculoskeletal conditions, they had very little awareness that physiotherapists work with children or other services available within the discipline's scope of practice 16 . Though limited, studies on public awareness across speech pathology, physiotherapy, occupational therapy, audiology, podiatry and chiropractic all highlight the need for educational campaigns to promote the full range of services offered by these allied health professions 7‐25 …”
Section: Discussionmentioning
confidence: 99%
“…The implication of these findings is that public awareness campaigns must be inclusive of those members of the community who do not have higher educational qualifications and have not previously had contact with the profession. One way to achieve this might be to specifically target medical practitioners as several of the studies on public perception on allied health professionals and communication disorders state that members of the public rely on doctors’ knowledge of their issues to make the appropriate referrals 8,10,16,17,22,31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian newspapers were chosen because (a) existing and potential nurses are readers of newspapers, (b) the database covers over 300 news sources covering all regions of Canada, (c) over 75% of Canadians still read newspapers [92,93] and as such, are influenced by what they read and (d) Parents, teachers, and career counselors who often give advice on career ideas to young adults are also readers of newspapers [94].…”
Section: Newspapersmentioning
confidence: 99%